Structure and Flame-Retardant Actions of Rigid Polyurethane Foams with Expandable Graphite - Chen, Yongjun (Polymers (Basel), 2019)
In this paper, rigid polyurethane foams that were filled with expandable graphite (RPUF/EG) composites were prepared by the liquid blending method, and then the structure and flame retardancy performance of materials were investigated through optical microscope, scanning electron microscope, limit oxygen index, cone calorimeter, thermogravimetric analysis coupled to fourier transform infrared spectrum, and X-ray photoelectron spectroscopy. The results showed that a large number of EG could be good to the exhibition of flame retardancy of RPUF, where the optimal material was found at loading 15 phr EG that showed an increased limit oxygen index value and a decreased calorific or fuming value. TGA coupled FTIR and XPS revealed that EG could disassembled before RPUF under heating treatment, and it could form a pyknotic and enahnced residual carbon layer on RPUF surface after the fire, which restricted the transfer of gas, like oxygen or heat into PU matrix, finally resulting in the promotion of flame retardancy of RPUF.